2020
DOI: 10.4014/jmb.2002.02059
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus casei LC01 Regulates Intestinal Epithelial Permeability through miR-144 Targeting of OCLN and ZO1

Abstract: Our previous report determined that miR-144 is a key regulator of intestinal epithelial permeability in irritable bowel syndrome with diarrhea (IBS-D) rats. Recent evidence has shown that lactobacilli play an important role in the relief of IBS-D symptoms. However, few studies have addressed the mechanisms by which microRNAs and lactobacilli exert their beneficial effects on intestinal epithelial permeability. Hence, to elucidate whether miRNAs and lactobacilli play roles in intestinal epithelial barrier regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Accordingly, the analysis of cell adhesion-related gene expression shows significant up-regulation of occludin and zonula occludens-1 (ZO-1), important tight junction proteins, in the intestine of the L. casei group. Our results are in agreement with previous studies, showing the role of lactobacilli on the intestinal epithelial barrier regulation (30,31).…”
Section: Discussionsupporting
confidence: 94%
“…Accordingly, the analysis of cell adhesion-related gene expression shows significant up-regulation of occludin and zonula occludens-1 (ZO-1), important tight junction proteins, in the intestine of the L. casei group. Our results are in agreement with previous studies, showing the role of lactobacilli on the intestinal epithelial barrier regulation (30,31).…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with other reports, lactobacilli are dominant in the ileum at the genus level [ 39 , 40 ]. Several studies have repeatedly shown that lactobacilli , as the most important microbiota in animal intestines, have various biochemical functions, including in the protection of the integrity of the intestinal mucosal, the invasion of pathogens, and stimulation of the immune system [ 41 , 42 ]. Many probiotic strains of lactobacilli have been widely used in poultry production [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tight junction proteins and mucins affect intestinal mucosal integrity ( 30 ). ZO1 is a tight junction protein that connects cells to form a barrier to protect the body from the contents of the intestine ( 31 ). The current study showed that dietary supplementation with 700 mg/kg PNZ could upregulate the gene expression of ZO1 better than ANT and NZO, which indicated that PNZ has a beneficial effect on barrier function and intestinal integrity.…”
Section: Discussionmentioning
confidence: 99%